Sustainable Environmental Education Through Local Potential Studies In The Gunungkidul Region Of Yogyakarta - Miftakhul Khasanah; Ixora Sartika Mercuriani; Suyitno Aloysius (Jurnal Penelitian Pendidikan IPA, 2025)
Environmental education plays a crucial role in shaping the character of students as the next generation, enabling them to be aware and concerned about environmental sustainability. Through environmental education, students are equipped not only with theoretical knowledge but also with practical values and skills to encourage them to become agents of change. This study aims to examine the Gunungkidul region as a source of local potential learning information on the topic of environmental change in science or biology learning materials for students. To support its learning activities, this study also adopts environmental education learning trends that can be used as part of efforts to build sustainable environmental education. This research is a literature review, focusing on articles published between 2020 and 2025 to ensure the data used is current and relevant. The results of the study indicate that the Gunungkidul region has great potential as a source of information for science or biology learning for students. In terms of environmental education learning, there are approaches, models, teaching materials, and learning media that teachers can choose or combine to improve the effectiveness of environmental education learning, especially on the topic of environmental change, with the hope that there will be no more gaps in the student learning process, so that student learning outcomes can be more meaningful and sustainable to support environmental sustainability in the future.